2014
DOI: 10.5194/tc-8-651-2014
|View full text |Cite
|
Sign up to set email alerts
|

Soil erosion and organic carbon export by wet snow avalanches

Abstract: Abstract. Many mountain belts sustain prolonged snow cover for parts of the year, although enquiries into rates of erosion in these landscapes have focused almost exclusively on the snow-free periods. This raises the question of whether annual snow cover contributes significantly to modulating rates of erosion in high-relief terrain. In this context, the sudden release of snow avalanches is a frequent and potentially relevant process, judging from the physical damage to subalpine forest ecosystems, and the amo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 42 publications
(38 reference statements)
0
11
0
Order By: Relevance
“…Further, erosion‐induced transport leads to differential removal of SOC fractions. The particulate organic C (POC) is removed preferentially by inter‐rill erosion (Wang et al., ; Wang, Cammeraat, Cerli, & Kalbitz, ), whereas the mineral‐bound organic C (MOC) is relatively protected (see Table ). Worrall, Burt, and Howden () observed that soil erosion is a source of GHGs and has emission factors of 5.5, 4.4, and 0.3 Mg CO 2 eq/year for one Mg of fluvial C, gross C erosion, and gross soil erosion, respectively.…”
Section: Soil Erosion and Soc Dynamicsmentioning
confidence: 99%
“…Further, erosion‐induced transport leads to differential removal of SOC fractions. The particulate organic C (POC) is removed preferentially by inter‐rill erosion (Wang et al., ; Wang, Cammeraat, Cerli, & Kalbitz, ), whereas the mineral‐bound organic C (MOC) is relatively protected (see Table ). Worrall, Burt, and Howden () observed that soil erosion is a source of GHGs and has emission factors of 5.5, 4.4, and 0.3 Mg CO 2 eq/year for one Mg of fluvial C, gross C erosion, and gross soil erosion, respectively.…”
Section: Soil Erosion and Soc Dynamicsmentioning
confidence: 99%
“…Wet avalanches in lacustrine deposits have been identified by Vasskog et al (2011) using grain size analysis to identify layers of poorly sorted grain accumulation associated with gravels resulting in a multi-modal grain size distribution. Such deposits on lake ice would result in drop stones at thaw season (Luckman, 1975), and may contain such deposits on lake ice would result in drop stones at thaw season, and may contain terrestrial organic matter (OM; Irmler et al, 2006;Wilhelm et al, 2013;Korup and Rixen, 2014).…”
mentioning
confidence: 99%
“…While the causes and effects of erosion as a soil degradation threat in the world are widely described and investigated (Lal, 2001), soil loss estimation in sloping areas still has some uncertainties, as the methods commonly used are not specifically designed for mountain environments, where climate and relief are extreme (Alewell et al, 2008;Garcia Rodriguez et al, 2012). Recently, the relevance of winter erosion processes, besides the ones taking place in the growing season, has been pointed out.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the relevance of winter erosion processes, besides the ones taking place in the growing season, has been pointed out. For example, Ceaglio et al (2012), and more recently Korup et al (2014), proved that snow movements are a significant agent of soil redistribution at mountain sites. Within these snow movements, wet avalanches are well known for their high sediment yields (Gardner, 1983;Ackroyd, 1987;Bell et al, 1990;Jomelli and Bertran, 2001;Heckmann et al, 2005); however, so far regionalization and parameterization of these processes are missing.…”
Section: Introductionmentioning
confidence: 99%